Peran Aliansi Masyarakat Adat Nusantara (AMAN) dalam Pencegahan Covid-19 di Wilayah Masyarakat Adat - Fatimah, Fatimah (Universitas Islam Balitar, 2023)
The role of the Indigenous Peoples Alliance Archipelago (AMAN) in overcoming Covid-19 in the territory of indigenous peoples is very large, it can be seen from the various strategies carried out by AMAN hand in hand to strive for various ways to deal with COVID-19 in indigenous peoples. The results of AMAN's research help deal with the pandemic by establishing a Covid-19 task force in indigenous territories, guarding the borders of indigenous villages, distributing masks and socializing to indigenous peoples how to transmit the Covid-19 virus, spraying disinfectants and providing knowledge of food security in the midst of this pandemic. However, on the other hand, indigenous peoples have their own way of dealing with this pandemic, namely with local wisdom that has been passed down from their ancestors centuries ago, this method is more trusted by indigenous peoples in dealing with disasters such as the Covid-19 pandemic.